2022
DOI: 10.1186/s42409-022-00041-2
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness worldwide: translation of the Duke University Religion Index into 20 languages and validation across 27 nations

Abstract: Religiousness and spirituality are important in the study of psychology for several reasons: They are central to identity and values; they have been reported as being positively associated with health and well-being; and they capture (and perhaps lead to) the largest measurable psychological differences between societies. At five items, the Duke University Religion Index (DUREL) is an efficient measure, which advantageously distinguishes between religious sentiment and activity, and between formal versus priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The decision to test a two-factor model—in addition to single- and three-factor models—was based on the statistical–theoretical tension already described. Several prior research teams identified a two-factor, best-fitting statistical model for their DUREL data—combining Items 1 and 2 into one factor and Items 3, 4, and 5 into a second factor (Cruz et al, 2017; Toscanelli et al, 2022). In addition, a conceptual justification may be made for a two-factor model, in that the first two items of the DUREL measure religious behaviors, while the remaining three items measure religious motivation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The decision to test a two-factor model—in addition to single- and three-factor models—was based on the statistical–theoretical tension already described. Several prior research teams identified a two-factor, best-fitting statistical model for their DUREL data—combining Items 1 and 2 into one factor and Items 3, 4, and 5 into a second factor (Cruz et al, 2017; Toscanelli et al, 2022). In addition, a conceptual justification may be made for a two-factor model, in that the first two items of the DUREL measure religious behaviors, while the remaining three items measure religious motivation.…”
Section: Discussionmentioning
confidence: 99%
“…A Google Scholar search revealed that the short form of the SCSRFQ has been cited 206 times, while the original DUREL article has been cited over 1,000 times. In addition, although the SCSRFQ has been translated into Spanish, Portuguese, Italian, Czech, Polish, German, Chinese, and Farsi (Plante, 2021), the DUREL has been translated into over 20 languages (Toscanelli et al, 2022). These facts highlight the importance of continuing the conversation about the psychometrics of the DUREL.…”
mentioning
confidence: 99%
See 3 more Smart Citations